Novel anti-endothelial therapeutic strategies in malignant melanoma : the metronomic approach. - Murray, Alexandra M. (2011)
Treatment strategies for advanced malignancy remain limited in their success, despite major advances in the understanding of cancer aetiology and molecular biology. The incidence of many cancers, including melanoma, continues to rise, with a huge demand for therapies even if treatment goals are purely cytostatic. One particular therapeutic strategy is the metronomic (continuous and low) dosing of conventional chemotherapy. There is evidence to suggest that tumour vasculature is the main target of this dosing schedule resulting in an overall ‘non specific’ anti-angiogenic effect. It is now being studied in clinical trials alone and in combination with specific antiangiogenic agents. This thesis had two main aims: firstly to investigate the additive or synergistic antiendothelial effects of a number of conventional cytotoxic agents (Temozolomide, Paclitaxel, Vinorelbine, Etoposide, Carboplatin) in vitro given in a metronomic schedule in combination with a specific anti-angiogenic compound (Sorafenib) and a non-specific sompound (Combretastatin). The anti-proliferative, cytotoxic activities of the metronomic combinatorial schedules were assessed on microvascular endothelial cells and cancer cells using an MTT proliferation assay. Results confirmed significant (p
HydraID: hull:5288 Hydra Discover Access Group: public ETD Collection: ETDPostgraduateMedicalInstitute
Keywords: Medicine